2019
DOI: 10.1155/2019/3737194
|View full text |Cite
|
Sign up to set email alerts
|

Parental Perceptions of Child’s Medical Care and Neighborhood and Child’s Behavioral Risk Factors for Obesity in U.S. Children by Body Mass Index Classification

Abstract: Environmental factors, preventive medical care, and behaviors play a role in childhood obesity. This study used the National Survey of Children's Health, 2011-2012, for 42,828 children, ages 10–17 years. Greater percent of children in the overweight/obese category performed no moderate-to-vigorous physical activity: 11.9 (10.6, 13.3) as compared to children in the underweight/normal weight category: 9.7 (8.9 10.6). No moderate-to-vigorous physical activity was associated with no preventive medical care, inadeq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…Third, youth who lacked parks were more likely to be overweight or obese. This finding replicates past reports about parks and child weight (50,51). Singh et al (2007) reported that U.S. children without parks had a 20% higher risk of obesity and a 22% higher risk of being overweight (2).…”
Section: Discussionsupporting
confidence: 83%
“…Third, youth who lacked parks were more likely to be overweight or obese. This finding replicates past reports about parks and child weight (50,51). Singh et al (2007) reported that U.S. children without parks had a 20% higher risk of obesity and a 22% higher risk of being overweight (2).…”
Section: Discussionsupporting
confidence: 83%